2017
DOI: 10.1016/j.bbi.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus serostatus, inflammation, and antibody response to influenza vaccination in older adults: The moderating effect of beta blockade

Abstract: Cytomegalovirus (CMV) has been implicated as a factor in immunosenescence, including poor antibody response to vaccination and higher immune activation and inflammation. Some people may be more or less vulnerable to the negative effects of CMV. The present investigation tested the effects of beta-blocker use and chronological age on the associations between CMV and immunity in adults aged 60–91 (N=98; 69% CMV seropositive) who were administered the trivalent influenza vaccine for up to 5 years. Peak antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The potential influence of latent CMV-infection on the antibody response to influenza vaccination was also investigated by extracting the association between the CMV antibody level and the influenza antibody titer. Five studies reported this outcome variable, either as a correlation between the CMV antibody level and the influenza antibody titer post-vaccination or using a regression model, in which additional factors than only CMV antibody level, such as age, were taken into account [25, 42, 47, 55, 56]. The five studies together reported 10 individual records (Supplementary figure 4) and included younger and older adults (18–97 years) and different influenza strains (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential influence of latent CMV-infection on the antibody response to influenza vaccination was also investigated by extracting the association between the CMV antibody level and the influenza antibody titer. Five studies reported this outcome variable, either as a correlation between the CMV antibody level and the influenza antibody titer post-vaccination or using a regression model, in which additional factors than only CMV antibody level, such as age, were taken into account [25, 42, 47, 55, 56]. The five studies together reported 10 individual records (Supplementary figure 4) and included younger and older adults (18–97 years) and different influenza strains (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, post-vaccination titers as outcome will overestimate the vaccine antibody response and are, therefore, less meaningful. Linear regression analysis, as performed in some studies [42, 63], is the best method to correct for pre-vaccination titers [46], but this could not be analyzed on the basis of the extracted data of the studies included for this review. Thus, with the GMR, the best outcome available, no effect of CMV seropositivity on the influenza vaccine response is observed.…”
Section: Discussionmentioning
confidence: 99%
“…A beneficial effect of latent CMV infection on the long-term persistence of protection after vaccination in adults has to our knowledge not been reported. Waning of protection is thought to be most significant in individuals above 65 years of age ( 45 ) and accelerated by latent CMV infection ( 46 ). Our results might suggest a positive effect of CMV infection in adults on the protection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a potential mechanism is apparent as the vascular system is a major battleground of viral infection and immunological control. The virus is tropic for endothelial cells (81) and indeed the large CMV-specific immune response within the vascular system is believed to represent 'immune surveillance' of the vascular bed (82)(83)(84). This association of CMV with cardiovascular disease may help to explain why some of the more recent epidemiological studies of CMV infection in older people have failed to replicate earlier studies.…”
Section: Infection In Older People Is Associated With An Excess Omentioning
confidence: 99%